EEG alpha power: An indicator of visual fatigue - Naqvi, S.A.A. (IEEE Computer Society, 2014)
There have been reports that some people who watch 3D movies experience motion sickness symptoms. In this research work, the change in dynamics of mental activity of subjects is evaluated to understand the reason behind the sickness. Cortical activity of the brain recorded from subjects who watch a stimulus (movie) on 2D and 3D TV. We propose that brain waves recorded using EEG device can be analysed using signal processing techniques and statistical methods. This will help in distinguishing between viewers of 2D and 3D stimulus, as well as being helpful in finding brain related areas that are active during the prevalence of motion sickness. Â© 2014 IEEE.